2017
DOI: 10.1002/cam4.1044
|View full text |Cite
|
Sign up to set email alerts
|

Trend analysis and survival of primary gallbladder cancer in the United States: a 1973–2009 population‐based study

Abstract: Primary gallbladder cancer is an aggressive and uncommon cancer with poor outcomes. Our study examines epidemiology, trend, and survival of gallbladder cancer in the United States from 1973 to 2009. We utilized the Surveillance Epidemiology and End Results database (SEER). Frequency and rate analyses on demographics, stage, and survival were compared among non‐Hispanic whites, Hispanics, African American, and Asian/Pacific Islanders. A total of 18,124 cases were reported in SEER from 1973 to 2009 comprising 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 20 publications
3
47
0
1
Order By: Relevance
“…In agreement with prior studies, we found that GBC incidence rates were highest among women, Hispanics, and older age groups . These differences between demographic groups in GBC incidence rates may be explained by variations in risk factor prevalence by sex and race/ethnicity.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with prior studies, we found that GBC incidence rates were highest among women, Hispanics, and older age groups . These differences between demographic groups in GBC incidence rates may be explained by variations in risk factor prevalence by sex and race/ethnicity.…”
Section: Discussionsupporting
confidence: 92%
“…GBCA is the most common biliary tract malignancy worldwide, and is associated with poor OS . The global incidence of GBCA varies strikingly, and there is support for a geographic influence on pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…First, the small sample size, although large in comparison with other published studies of this type, limits the power to make definitive conclusions. The low incidence of GBCA restricts the number of patients who can be enrolled in these studies . Second, the retrospective nature of the current study introduces inherent limitations, such as selection biases and heterogeneous samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Analysis from SEER data from 1973 to 2009 showed that out of total cases diagnosed, the proportion of cases that are diagnosed as distant disease (Vs regional and localized disease) is increasing over time. [2] Brain metastasis in carcinoma gallbladder is extremely rare and only 8-10 cases are reported in English literature.…”
Section: Introductionmentioning
confidence: 99%